2008
DOI: 10.1007/s00246-008-9304-2
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Myxoma After Treatment for Childhood Neuroblastoma

Abstract: An asymptomatic 13 year old with a history of neuroblastoma treated with chemotherapy, radiation therapy, and autologous bone marrow transplant was found to have a cardiac mass on screening echocardiogram. Surgical resection and histologic examination revealed the mass was a myxoma. After resection the patient made a full recovery. This report reviews the features of myxoma and explores the potential relationship between chemotherapy, radiation, bone marrow transplant and myxoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Myxomas have been reported in a few patients after immunosuppression for solid organ transplant [9]. Inflammation also appears to be a trigger for CLL development [10].…”
Section: Discussionmentioning
confidence: 99%
“…Myxomas have been reported in a few patients after immunosuppression for solid organ transplant [9]. Inflammation also appears to be a trigger for CLL development [10].…”
Section: Discussionmentioning
confidence: 99%
“…Hill et al reported an incidental case of cardiac myxoma in a child with neuroblastoma as well but after 5.5 years of being off therapy who also survived after complete resection of the tumour. 6 Due to the possibility of cardiac myxoma embolism and the risk of sudden death, surgery should be performed as soon as possible once cardiac myxoma is diagnosed to remove as much of the tissue surrounding the tumour as possible and reduce the recurrence rate. 7 In conclusion, our case describes incidental finding of cardiac lesion in a child with neuroblastoma that mimicked a cardiac thrombus at initial finding.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of diagnosis suspicion bias, the knowledge that the patient has been diagnosed with one disease (neoplasm) influences the intensity of their search for another condition. 10 Some case reports, however, describe cardiac myxomas as a late complication in cancer survivors, hypothesizing that chemotherapy, radiotherapy, or immunosuppression [11][12][13] may have contributed to the tumor's growth. 14,15 Cardiac tumors are rare, and any spaceoccupying mass noted on cardiovascular imaging modalities should be considered as part of the differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%